2022
DOI: 10.3389/fmicb.2022.718786
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Bacillus subtilis Against SARS-CoV-2 – A Sustainable Drug Development Perspective

Abstract: The COVID-19 pandemic had anomalous yet inevitable impacts on the world’s economies, healthcare systems, and all other aspects of life. Researchers began to uncover hidden routes to find a new horizon of hope using underrated resources. Biosurfactants are sustainable biomolecules with an active surface, unique characteristics, and extensive uses. Bacillus species showed the highest amount of biosurfactant activities and Bacillus subtilis is one of them. The antiviral, antimicrobial, and anti-inflammatory activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…During the COVID-19, in order to prevent and control cross-infection and spread, government departments implement measures such as public health pandemic prevention, personnel isolation and travel restrictions, resulting in a sharp decline in population mobility, causing the direct blockade in terms of people, logistics and commodity flow ( 33 ). Due to it most people are isolated at home, and the out-of-home consumption activities plummet sharply, which reduce the consumption and demand of products and services, causing the original inventory backlog of firms, the increase of the inventory cost, and the reduction of firm profits.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…During the COVID-19, in order to prevent and control cross-infection and spread, government departments implement measures such as public health pandemic prevention, personnel isolation and travel restrictions, resulting in a sharp decline in population mobility, causing the direct blockade in terms of people, logistics and commodity flow ( 33 ). Due to it most people are isolated at home, and the out-of-home consumption activities plummet sharply, which reduce the consumption and demand of products and services, causing the original inventory backlog of firms, the increase of the inventory cost, and the reduction of firm profits.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Scientists are committed to finding appropriate methods for the pandemic to treat and control its spread. Researchers from all disciplines come together to provide expertise (6)(7)(8)(9)(10)(11) as the COVID-19 pandemic unfolds. Viral ribonucleic acids can be detected by real-time polymerase chain reaction.…”
Section: Technicalmentioning
confidence: 99%
“…A large amount of academic literature on COVID-19 has been emerging in many disciplines, including a great deal of metaresearch summarizing ongoing vaccine development or even drug discovery (3)(4)(5) and published papers (6)(7)(8)(9)(10)(11). In addition, there is a rapidly emerging COVID-19 patent literature, despite the short time since the pandemic began.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, numerous clinical trials to assess the potential of existing licensed drugs with well-established safety profiles have been conducted or are underway on COVID-19 patients to accelerate the identification of appropriate medication for treatment or prevention of infection. In preclinical studies, various repurposed drugs have been demonstrated as potential inhibitors of one or more steps of the SARS-CoV-2 lifecycle ( 6 8 , 10 12 ). However, evidence from primary studies is inadequate, and more recent reports from large-scale clinical trials are needed.…”
Section: Introductionmentioning
confidence: 99%